In vivo Two-Photon Imaging Reveals Acute Cerebral Vascular Spasm and Microthrombosis After Mild Traumatic Brain Injury in Mice - Han, Xinjia; Chai, Zhi; Ping, Xingjie; Song, Li-Juan; Ma, Cungen; Ruan, Yiwen; Jin, Xiaoming (Frontiers in Neuroscience, 2020)
Mild traumatic brain injury (mTBI), or concussion, is reported to interfere with cerebral blood flow and microcirculation in patients, but our current understanding is quite limited and the results are often controversial. Here we used longitudinal in vivo two-photon imaging to investigate dynamic changes in cerebral vessels and velocities of red blood cells (RBC) following mTBI. Closed-head mTBI induced using a controlled cortical impact device resulted in a significant reduction of dwell time in a Rotarod test but no significant change in water maze test. Cerebral blood vessels were repeatedly imaged through a thinned skull window at baseline, 0.5h, 1h, 6h, and 1day following mTBI. In both arterioles and capillaries, their diameters and RBC velocities were significantly decreased at 0.5, 1, and 6 h after injury, and recovered in 1 day post-mTBI. In contrast, decreases in the diameter and RBC velocity of venules occurred only in 0.5-1 h after mTBI. We also observed formation and clearance of transient microthrombi in capillaries within 1 h post-mTBI. We concluded that in vivo two-photon imaging is useful for studying earlier alteration of vascular dynamics after mTBI and that mTBI induced reduction of cerebral blood flow, vasospasm, and formation of microthrombi in the acute stage following injury. These changes may contribute to early brain functional deficits of mTBI.